Penyuluhan Gaya Hidup Sehat Untuk Mengurangi Risiko Penyakit Paru Obstruktif Kronis (PPOK) - Dia Rejeki Utami; Sudirman Sudirman; Nurul Aisyisyah P; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease that is a leading cause of morbidity and mortality worldwide. COPD develops progressively and is often diagnosed only at an advanced stage due to low public awareness of risk factors and prevention efforts. The main risk factors for COPD include smoking, exposure to air pollution, and an unhealthy lifestyle. This Community Service activity aims to increase public knowledge and awareness regarding the importance of adopting a healthy lifestyle to reduce the risk of COPD. Implementation methods included health education, interactive discussions, education on clean and healthy living behaviors, and evaluation through pre- and post-tests. The results of the activity showed an increase in public knowledge and changes in attitudes toward COPD-risk behaviors. Healthy lifestyle education is expected to contribute to COPD prevention efforts and improve the community's quality of life.